Burning Mouth Syndrome and Other Oral Sensory Disorders: A Unifying Hypothesis - Miriam Grushka; Joel B Epstein; Meir Gorsky (Pain Research and Management)
Burning Mouth Syndrome (BMS) is a sensory disorder which results in constant, bilateral burning pain of the tongue, lips, and other oral mucous membranes. Atypical odontalgia (AO) is another sensory disorder, usually defined as a toothache-like pain for which no dental cause can be identified. Previous literature has suggested that AO is often associated with a concomitant temporomandibular disorder (TMD). This hypothesis paper explores the possibility that BMS, AO and TMD can be related through hyperactivity of both the sensory and motor components of the trigeminal nerve following loss of central inhibition as a result of taste damage in the chorda tympani and/or the glossopharyngeal nerves.